SISTEM INFORMASI PEMBAYARAN KOS BERBASIS NOTIFIKASI WHATSAPP GATEWAY PADA KOS ANGELIKA 3 - Selestina Amelia Nago; nikson fallo (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2022)
Boarding houses are home for many people in academic or remote work environments. In its management, an effective and efficent payment system is needed to ensure that payments from boarding houses residents are fulfilled in a timely and accurate manner. The payment process is currently carried out every month with payement daya processing still using a manual system, namely recording it in a payment notebook. This creates obstacles in checking data on tenants who have paid or not. Tis manual process takes quite a long time because you have to check payemnt logbook one by one. Apart from that, other obstacles facced include payments errors, late payments, lost billing sheets and the need for extra time and energy for boarding payment transaction data. Therefore, it is necessary to build a web-based boarding house payment information system so that boarding house bills and confirm payments, so that the efficiency of boarding house management can be increased and can minimize errors that occur when using the old system using the manual book recording method